Pharmacological Factors that May Influence Myocardial Changes Associated with Atherosclerosis - Bedel, Cihan; Bedel, Hatice Aslı (National Journal of Medical Research, 2025)
We read with great interest the article recently published by Patel et al. entitled “Histological and Morphometric Analysis with Grading of Atherosclerosis-Associated Myocardial Changes in Cases of Sudden Death at a Tertiary Care Hospital”.1 They found that a comprehensive evalu-ation combining histological grading and morphometric analysis is crucial for a thorough understanding of atherosclerosis-related myocardial changes. We congratulate them for their valuable contributions to the literature.